Online and Face-to-Face Learning during COVID-19 Pandemic: A Comparative Analysis of Instructors and Student's Performance - Khanda Gharib Aziz; Bawar Mohammed Faraj; Khalan Jalil Rostam (CV FOUNDAE, 2022)
The COVID-19 pandemic necessitated a sudden shift to online learning, prompting discussions on its effectiveness compared to traditional face-to-face methods, especially in higher education contexts. This study explores the perception of teachers and students regarding online learning's advantages, disadvantages, and recommendations. A quantitative case study was conducted from April to December 2021, involving 81 participants (teachers and students) from various disciplines, including science, law, administration, agriculture, and economics.Data were analyzed using Pearson’s correlation and Chi-square tests with SPSS version 25. The study identified that online learning offers flexibility and supports lifelong learning. However, inefficiencies were noted in teaching practical skills, and significant weaknesses were observed in student-teacher and student-student interactions. Additionally, online learning posed challenges in preventing academic dishonesty. The findings highlight the need for improved strategies to enhance interaction, practical skill development, and quality assurance in online education. Policymakers and educators should consider these insights to develop more robust online learning frameworks.